2023
DOI: 10.3390/su15021406
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Enhancement of Gaseous Elemental Mercury Using Waste Steel Slag under Various Experimental Conditions

Abstract: In this study, the oxidation characteristics of elemental mercury were assessed based on the input gas environment, temperature, and particle size distribution of the steel slag. Experiments were performed at room temperature, 100 °C and 200 °C, under air and simulated gas environments. The oxidation reaction of elemental mercury was conducted using steel slag samples of 1 mm, 2.36 mm, and 4.75 mm at various conditions. From the basic characteristic analysis of the steel slag, it was found that the steel slag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…According to previous studies, mercury removal can be effectively improved by increasing the adsorbent dosage [27]. Obviously, in practical applications, the dosage of the AC will be much higher than the milligram level to ensure operational stability and long-term durability [28][29][30]. Therefore, it can be concluded that the AC exhibits a relatively wide range of capabilities for removing Hg 0 from nonferrous smelting flue gases.…”
Section: Effect Of Temperature On Mercury Removal Performancementioning
confidence: 99%
“…According to previous studies, mercury removal can be effectively improved by increasing the adsorbent dosage [27]. Obviously, in practical applications, the dosage of the AC will be much higher than the milligram level to ensure operational stability and long-term durability [28][29][30]. Therefore, it can be concluded that the AC exhibits a relatively wide range of capabilities for removing Hg 0 from nonferrous smelting flue gases.…”
Section: Effect Of Temperature On Mercury Removal Performancementioning
confidence: 99%
“…The higher P 2 O 5 content inhibited the conversion of β-C 2 S to γ-C 2 S and hindered the self-powdering of steel slag. The transformation of β-C 2 S to γ-C 2 S in the slag produces a volume expansion of about 11%, allowing the slag to undergo self-powdering [10][11][12]. Chuan-ming Du et al [13] investigated the effect of Fe 2+ (Fe 2+ /T.Fe) content on the leaching solid solution of P 2 O 5 using the leaching of concentrated phosphorous solid solution from steel slag.…”
Section: Introductionmentioning
confidence: 99%